Nostalgic representation of reality in television fiction: an empirical study based on the analysis of the Spanish television series Cuéntame cómo pasó - Martín Oller Alonso; Daniel Barredo Ibáñez (Revista Mediterránea de Comunicación, 2012)
The Spanish transition from dictatorship to democracy is often described as an example of negotiation or agreement between the elites (Sánchez Cuenca and Aguilar, 2009: 433). Journalistic and political elites, aware of their important historical role, agreed a consensus on certain issues (democracy, constitution, amnesty) or characters (King Juan Carlos I), in order to ensure the stability of the democratic process (Zugasti, 2007, 2008). Television, which articulates the discourse of the masses, has been one of the basic means used to illustrate the development. Among the highlights of recent major audiovisual content, Cuéntame cómo pasó (2001-present) -a TV-series designed to explain changes with a nostalgic tone in Spanish society since 1968 until today- stands out. By choosing a random sample of episodes for this research we propose to verify the validity of the representation of the political process which contextualizes the series. By analyzing many elements, such as the opinions of the main characters, their personal, political and geographical situations, we try to show the construction of a focal point that sanctifies the official version. We also stress the pacifying and nostalgic tone, which constructs stereotypes and taboos about the process and which characterizes this series as a symbolic culmination of the democratization undertaken by the elites.